Medication adherence among patients with apparent treatment-resistant hypertension: systematic review and meta-analysis - Durand, Hannah; Hayes, Peter; Morrissey, Eimear C; Newell, John; Casey, Monica; Murphy, Andrew W; Molloy, Gerard J (Journal of hypertension, 2017)
Medication nonadherence is a known behavioural contributor to poor blood pressure (BP) control that puts patients with hypertension at elevated cardiovascular risk. Studies of medication adherence for apparent treatment-resistant hypertension (aTRH) vary significantly with respect to design, methods, and setting, and, as a result, have produced highly variable figures describing the prevalence of nonadherence. This review aimed to describe the prevalence and potential moderators of medication nonadherence estimates for aTRH. Systematic review and random effects meta-analysis. From an initial discovery of 921 studies, we identified 24 studies that measured medication adherence for patients with uncontrolled BP despite being prescribed three or more antihypertensive medications of different classes. By using a random effects model, the pooled prevalence of nonadherence was 31.2% (95% confidence interval = 20.2-44.7, I = 99.50) with nonadherence rates ranging from 3.3 to 86.1%. The strongest contributor to variance in nonadherence rates was the method of adherence assessment used. Studies that relied on self-report measures of adherence and/or pharmacy data reported lower levels of nonadherence than studies using more objective methods, such as liquid chromatography-mass spectrometry in single time-point bioassays or directly observed therapy. Findings indicate that medication nonadherence is a significant problem among aTRH patients. Identifying the most accurate and clinically feasible adherence assessment methods is necessary to reduce BP and cardiovascular morbidity, facilitate early behavioural intervention, prevent unnecessary diagnostic testing, and limit sometimes unnecessary and expensive BP lowering procedures. CRD42016028121.